The influence of polymer purification on the efficiency of poly(3-hexylthiophene):fullerene organic solar cells - Bannock,JH; Treat,N; Chabinyc,M; Stingelin,N; Heeney,M; de,Mello JC (Scientific Reports, 2016)
We report the influence of different polymer purification procedures on the photovoltaic performance ofbulk heterojunction solar cells formed from binary blends of poly(3-hexylthiophene) (P3HT) andfullerenes. Selective Soxhlet extractions and metal scavenging agents were used to remove residualmonomer, magnesium salt by-products and catalyst from high-weight P3HT (Mw 121 kg/mol, PDI 1.8,RR 99%) synthesised by the Grignard metathesis (GRIM) polymerization route. Using phenyl-C61-butyric acid methyl ester (PC60BM) as an electron acceptor, we observed an increase in average powerconversion efficiency from 2.3 to 4.8 % in going from crude to fully purified material. Using indene-C60bisadduct (IC60BA) in place of PC60BM, we observed a further increase to an average value of 6.6 %,which is high for a bulk heterojunction formed from a binary blend of P3HT and C60 fullerene derivatives.